An Industry Perspective: Dietary Supplements and Mortality Rates in Older Women. (1st June 2013) - Wallace, Taylor C.; MacKay, Douglas; Ritz, Barry W.; McBurney, Michael; Shao, Andrew; Miller, John; Brooks, James; Hendricks, Lewis
ABSTRACT: This special article seeks to provide balance and clarity to the confusion brought about by the conclusions resulting from a recent study published in Archives of Internal Medicine by Mursu et al. (2011). An examination of three key limitations of the study provides context to why additional research is needed: (a) Nonusers were poorly defined; (b) supplement users were healthier than nonusers; and (c) the number of supplement users increased throughout the study. Although the literature is limited, other similar observational studies have also shown positive effects on the risk mortality for both multivitamins and single-nutrient supplements. Observational trials are an essential component of evidence-based nutrition but do not offer certainty because other data, such as the one generated from randomized controlled trials, are equally important in regard to the totality of evidence. The Senior Scientific Advisory Committee for the Council for Responsible Nutrition, an industry trade group, feels that the conclusions of the study by Mursu et al. (2011) are overstated and suggests that researchers analyze cohort(s) designed to specifically examine vitamin and mineral supplements free of confounding from factors, such as hormone replacement therapy, to better assess their benefits to the general population.